2010
DOI: 10.1111/j.1600-0897.2010.00936.x
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis is Induced in Chlamydia trachomatis-infected HEp-2 Cells by the Addition of a Combination Innate Immune Activation Compounds and the Inhibitor Wedelolactone

Abstract: This is the first time that induction of apoptosis has been reported in C. trachomatis-infected cells when treated with a combination of innate immune activators and wedelolactone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Moreover, recent data have demonstrated that wedelolactone significantly repressed the level of phosphorylated inhibitor of nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) and p65 [33][34][35][36]. Here, we demonstrated that wedelolactone has antioxidative effect through inhibiting IKK activity and p65 expression by EMSA.…”
Section: Discussionmentioning
confidence: 54%
“…Moreover, recent data have demonstrated that wedelolactone significantly repressed the level of phosphorylated inhibitor of nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) and p65 [33][34][35][36]. Here, we demonstrated that wedelolactone has antioxidative effect through inhibiting IKK activity and p65 expression by EMSA.…”
Section: Discussionmentioning
confidence: 54%
“…Ac-YVAD-CHO was used at a concentration of 10 μM (Garcia-Calvo et al, 1998), and replaced daily. Wedelolactone was used at 2 μM concentration [18]. Both PD98059 and U0126 were used at a concentration of 10 μM.…”
Section: Methodsmentioning
confidence: 99%
“…IL‐10 down‐regulates NO induced by other pathogens including P. brasiliensis (Moreira et al ., ) and parasites (Gazzinelli et al ., ), and macrophages deficient in IL‐10 kill C. pneumoniae better than the wild‐type macrophages, which appears to be related to iNOS (Rothfuchs et al ., ). In addition, mechanisms of host cell death, which are effected by NO in other infections (Ulett & Adderson, ), are modulated by Chlamydia in various cell types including epithelial cells, T lymphocytes, and macrophages (Yaraei et al ., ; Huston et al ., ; Olivares‐Zavaleta et al ., ). Modulation of host cell death (including inhibition of) by Chlamydia has also been linked to altered redox (Sessa et al ., ) and ROS (Vardhan et al ., ), among other mechanisms as reviewed elsewhere (Sharma & Rudel, ).…”
Section: Newly Discovered Microbial Triggers Of Il‐10 In the Hostmentioning
confidence: 99%